2019
DOI: 10.1111/tid.13124
|View full text |Cite
|
Sign up to set email alerts
|

IL28B rs12979860 T allele protects against CMV disease in liver transplant recipients in the post‐prophylaxis and late period

Abstract: Human cytomegalovirus (CMV) belongs to the Betaherpesvirinae subfamily. 1 CMV represents frequent opportunistic infection among solid organ transplant (SOT) recipients increasing their morbidity and mortality, particularly in patients with no pre-existing CMV-specific immunity. 2,3 Two major types of CMV infection are known to occur in SOT recipients. Primary infection is observed in CMV seronegative recipients (R−) who receive an allograft from a CMV seropositive, Abstract Background: Cytomegalovirus (CMV) di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Even though we cannot affirm the following, a suggested explanation for the delayed elevation of the specific IgG levels for COVID-19 in the volunteers who presented allele 1 (C/C) could be associated with CMV seropositivity, since in this subgroup of volunteers we found a negative correlation between the specific IgG levels for SARS-CoV-2 and CMV at the MO time-point. These data corroborate the literature, since it has been reported that individuals with genotypes CT or TT presented better control of CMV replication following primary infection than individuals presenting genotype CC, due to the upregulation of interferon-sensitive genes (ISGs), which acts in the inhibition of viral replication [ 71 , 72 ]. So, this result allows us to putatively suggest that IFN-lambda polymorphism in CMV-seropositive patients can impact response to SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Even though we cannot affirm the following, a suggested explanation for the delayed elevation of the specific IgG levels for COVID-19 in the volunteers who presented allele 1 (C/C) could be associated with CMV seropositivity, since in this subgroup of volunteers we found a negative correlation between the specific IgG levels for SARS-CoV-2 and CMV at the MO time-point. These data corroborate the literature, since it has been reported that individuals with genotypes CT or TT presented better control of CMV replication following primary infection than individuals presenting genotype CC, due to the upregulation of interferon-sensitive genes (ISGs), which acts in the inhibition of viral replication [ 71 , 72 ]. So, this result allows us to putatively suggest that IFN-lambda polymorphism in CMV-seropositive patients can impact response to SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 88%
“…In fact, according to the literature, it has been reported that the presence of allele 2 (T/T) is associated not only with lower replication permission and incidence of active CMV infection, but also with higher gene expression for IFNs than the presence of allele 1 (C/C) and heterozygous patients [ 69 , 72 ]. Furthermore, Bravo and collaborators [ 68 ] showed that patients undergoing allogeneic stem cell transplantation with allele 2 (T/T) in the IFN-lambda-3 gene showed a shorter duration of the first episodes of CMV infection than patients with allele 1 (C/C) and heterozygous patients (C/T).…”
Section: Discussionmentioning
confidence: 99%
“…In line with that, IFNL4 rs12979860 T is also associated with an impaired HCV clearance 15 . Finally, studies in the hematopoietic stem cell and solid organ transplant setting have reported an association of CMV replication with the IFNL4 rs368234815 ΔG as well as the rs12979860 T allele 20–22 …”
Section: Introductionmentioning
confidence: 55%
“…15 Finally, studies in the hematopoietic stem cell and solid organ transplant setting have reported an association of CMV replication with the IFNL4 rs368234815 ΔG as well as the rs12979860 T allele. [20][21][22] Currently, there are no reports that interrogate the association between BKPyV replication and IFNL4 polymorphisms in KTR and their donors. With this study, we aim (i) to determine the prevalence of the different SNP variants of the IFNL4 gene, and (ii) to evaluate the association of genetic IFNL4 variants, with the incidence of BKPyV reactivation and BKPyVAN in a Caucasian population of KTR.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that prophylaxis after transplantation significantly reduces the risk of CMV infection (8,9). Without a prevention strategy, CMV infection and disease typically occurs within the first three months after SOT.…”
Section: Introductionmentioning
confidence: 99%